Digital Banks : Lessons from Korea - Choi, Youjin (World Bank, Seoul, 2020)
Digital banks have been on the rise as digital technologies transform financial services around the world. Under the Korean government’s new policy framework for digital banks, K Bank and Kakao Bank successfully launched in 2017 with convenient and innovative products and services and brought a substantial impact on Korea’s banking sector. With their businesses growing at a fast pace, these banks sought to increase their capital accordingly, but encountered unforeseen regulatory issues on bank ownership which required new legislation and regulatory efforts to get resolved. After the first three years of operation, as of July 2020, the two banks show contrasting track records, mainly explained by differing challenges and successes in capital increase and marketing. With digital transformation accelerating and competition heightening, digital banks will need to become even more strategic and innovative to continue to be successful. This knowledge note was written to take stock of Korea’s experience with digital banks and share lessons that may be useful for financial policymakers and market players in banking and fintech.